Internet use by patients with bipolar disorder: Results from an international multisite survey. (30th August 2016) - Bauer, Rita; Conell, Jörn; Glenn, Tasha; Alda, Martin; Ardau, Raffaella; Baune, Bernhard T.; Berk, Michael; Bersudsky, Yuly; Bilderbeck, Amy; Bocchetta, Alberto; Bossini, Letizia; Castro, Angela M. Paredes; et al.
Abstract: There is considerable international interest in online education of patients with bipolar disorder, yet little understanding of how patients use the Internet and other sources to seek information. 1171 patients with a diagnosis of bipolar disorder in 17 countries completed a paper-based, anonymous survey. 81% of the patients used the Internet, a percentage similar to the general public. Older age, less education, and challenges in country telecommunications infrastructure and demographics decreased the odds of using the Internet. About 78% of the Internet users looked online for information on bipolar disorder or 63% of the total sample. More years of education in relation to the country mean, and feeling very confident about managing life decreased the odds of seeking information on bipolar disorder online, while having attended support groups increased the odds. Patients who looked online for information on bipolar disorder consulted medical professionals plus a mean of 2.3 other information sources such as books, physician handouts, and others with bipolar disorder. Patients not using the Internet consulted medical professionals plus a mean of 1.6 other information sources. The percentage of patients with bipolar disorder who use the Internet is about the same as the general public. Other information sources remain important. Highlights: Paper-based survey on Internet usage of 1171 patients with BP from 17 countries The percentage of Internet users is similar to that of the general public (81%). 78% of Internet users searched for information about BP, or 63% of total sample. All patients used multiple sources of information about BP. Web sites about BP are valuable, but other information sources remain important.